In vivo measurement of hemodynamic information in stenosed rat blood vessels using X-ray PIV - Park, Hanwook (Nature Publishing Group, 2016)
Measurements of the hemodynamic information of blood flows, especially wall shear stress (WSS), in animal models with circulatory vascular diseases (CVDs) are important to understand the pathological mechanism of CVDs. In this study, X-ray particle image velocimetry (PIV) with high spatial resolution was applied to obtain velocity field information in stenosed blood vessels with high WSS. 3D clips fabricated with a 3D printer were applied to the abdominal aorta of a rat cadaver to induce artificial stenosis in the real blood vessel of an animal model. The velocity and WSS information of blood flows in the stenosed vessel were obtained and compared at various stenosis severities. In vivo measurement was also conducted by fastening a stenotic clip on a live rat model through surgical intervention to reduce the flow rate to match the limited temporal resolution of the present X-ray PIV system. Further improvement of the temporal resolution of the system might be able to provide in vivo measurements of hemodynamic information from animal disease models under physiological conditions. The present results would be helpful for understanding the relation between hemodynamic characteristics and the pathological mechanism in animal CVD models.